2021
DOI: 10.1111/nph.17359
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophic growth of the extremophile Galdieria sulphuraria reveals the flexibility of its carbon assimilation metabolism

Abstract: Galdieria sulphuraria is a cosmopolitan microalga found in volcanic hot springs and calderas. It grows at low pH in photoautotrophic (use of light as a source of energy) or heterotrophic (respiration as a source of energy) conditions, using an unusually broad range of organic carbon sources. Previous data suggested that G. sulphuraria cannot grow mixotrophically (simultaneously exploiting light and organic carbon as energy sources), its photosynthetic machinery being repressed by organic carbon.Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 70 publications
5
25
0
Order By: Relevance
“…This confirms the ability of G. sulphuraria to cope with stress caused by high light using metabolic modulation [78]. In the case of mixotrophic growth, it could also be caused by the increase in intracellular CO 2 in Galdieria [79]. Interestingly, the DMs achieved were comparable under both trophic regimes at 40 • C and 750 µmol photons m −2 s −1 (Table 1), suggesting the need for further studies, particularly of photosynthetic performance.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This confirms the ability of G. sulphuraria to cope with stress caused by high light using metabolic modulation [78]. In the case of mixotrophic growth, it could also be caused by the increase in intracellular CO 2 in Galdieria [79]. Interestingly, the DMs achieved were comparable under both trophic regimes at 40 • C and 750 µmol photons m −2 s −1 (Table 1), suggesting the need for further studies, particularly of photosynthetic performance.…”
Section: Discussionsupporting
confidence: 63%
“…Evaluation of photosynthetic parameters of G. sulphuraria affected by different trophic regimes and growth conditions, especially in the context of photo-inhibition under high light intensities, would be a relevant future research direction. For example, photosynthesis of mixotrophic G. sulphuraria was boosted by enhancing carboxylation activity of Rubisco and decreasing photorespiration [79]. Similarly, Rubisco was affected by different trophic regimes in G. phlegrea [84].…”
Section: Discussionmentioning
confidence: 99%
“…This is, e.g., the case of some Chlorella species (e.g., Chlorella sorokininana ; Cecchin et al, 2018 , see, however, Zhang et al, 2017 for a different conclusion in Chlorella zoofingensis ) and of the diatom Phaeodactylum tricornutum ( Liu et al, 2009 ; Villanova et al, 2017 ). In the green oleaginous alga Ettlia oleoabundans and the red extremophyle alga Galdieria sulphuraria , mixotrophy stimulates both photosynthesis and respiration ( Ferroni et al, 2018 ; Curien et al, 2021 ). Overall, these findings indicate that while respiration is always increased by the addition of organic carbon, the photosynthetic responses change according to the nature of the microalga considered.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing respiration could be sufficient to fulfill the cell energy requirement for growth, via, e.g., enhanced consumption of cell reserves, under conditions where contribution by photosynthesis is relatively low. Conversely enhanced respiration could boost photosynthesis by providing extra CO 2 for carbon assimilation, provided that the photosynthetic apparatus is not dismantled by the addition of exogenous carbon sources ( Ferroni et al, 2018 ; Curien et al, 2021 ). Finally, respiratory consumption of organic compounds may be incomplete, allowing a (partial) direct utilization of their carbon scaffolds for anabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggested maintenance of photosynthesis in mixotrophic growth may depend on species and/or organic substrate ( Kamalanathan et al, 2017 ; Cecchin et al, 2018 ). Organic C supply can even support photosynthesis by reducing photoinhibition or improving CO 2 supply ( Xie et al, 2016 ; Curien et al, 2021 ; Gain et al, 2021 ) and Chlamydomonas cells also show regulation of inorganic carbon acquisition in response to organic C supply, possibly by stimulating respiratory CO 2 production inside cells which can be used for photosynthesis ( Fett & Coleman, 1994 ). However, some species need a light supply to be able to use glucose or to maximize growth benefit of organic C ( Chioccioli, Hankamer & Ross, 2014 ; Curien et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%